Competence Improvement Among Civil Servants at The Employee and Human Resource Development Departement in Probolinggo City - Hartati, Sri (Jurnal MSDA (Manajemen Sumber Daya Aparatur), 2023)
Development is imperative for cultivating competent state civil servants in their respective fields of work. This study is designed to describe and analyze the Competency Development of Civil Servants holding echelon III positions at BKPSDM Probolinggo City, utilizing a qualitative approach. The data collection process encompasses observation, interviews, and documentation, while data analysis involves techniques such as data reduction, data presentation, and drawing conclusions. The findings reveal that the development of echelon III officials at BKPSDM Probolinggo City, executed through education, training, and transfers, has not achieved optimal results. This suboptimal outcome can be attributed to several factors, including a constrained budget, inadequate training and education facilities, and low motivation, particularly among female civil servants grappling with the challenges of balancing their dual roles in the public and domestic spheres.